Taman Wisata Edukasi di Kota Makassar - Aulia Ilma Nur Aisyah; Abd. Azis Alimuddin; Andas Budy (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
The design of the Educational Tourism Park in Makassar aims to present an educational facility packaged with a recreational approach, making reading and learning activities more enjoyable and engaging. The term “park” here does not refer to a green open space area, but rather represents a concept of space that is friendly, open, and inviting—similar to the atmosphere of a garden that is welcoming, interactive, and appealing. The main facility, a library, is designed to serve as an informal educational hub accessible to all, especially the younger generation. This library is complemented by educational play areas, discussion spaces, and interactive zones to enrich the learning experience. The design adopts a modern tropical architectural approach, combined with green building principles, integrating both educational and recreational elements to create a holistic learning environment. The research applies a descriptive qualitative method, utilizing primary data through field observations and interviews, as well as secondary data from literature studies and similar design references. It is expected that the presence of this building will contribute significantly to revitalizing public interest in literacy, enriching public facilities in Makassar, and providing an inclusive as well as recreational educational public space.